Lente in die Teologie : 'n opwindende ligstraal van hoop vir die kerk - Muller, J.C. (Verbum et ecclesia, 2007)
The theology of springtime: an exciting ray of hope for the church Despite popular opinion, current theology is still in the midst of winter. In this article the nature of spring - of it as the in-between season - is taken as a metaphor for theology: between the lines and prior to the middle. It is a theology beyond fundamentalism whilst preceding relativism. It is a theology in-between the equilibrium of orthodoxy and orthodox practices; in-between confidence and anxiety; prior to right and wrong. It is highly contextual and with people! A spring theology reminds of so many imperative aspects of Practical Theology: people, uncertainty, deconstruction and imagination. This understanding of theology is explained by reference to three relevant issues: (a) gay persons, who have no place in modernistic theology, (b) people with HIV / Aids who have left the church perplexed, ignorant and without large and successful intervention practices and (c) understanding about the creation of the cosmos to those who still accept, adamantly, the Biblical version of creation (of even theorise about it).